The Impact of Digital Payment and Accessibility on Passenger Satisfaction with Service Quality as an Intervening Variable - Steven Owen Purnawan; Sigit Hermawan; Rita Ambarwati Sukmono; Zatul Karamah Ahmad Baharul Ulum; Tariq Tawfeeq Yousif Alabdullah (Jurnal Organisasi dan Manajemen, 2025)
Purpose – This study aims to test the hypothesis that digital payment methods and accessibility positively affect passenger satisfaction, with service quality as an intervening variable in Trans Jatim.  Methodology – We uses SmartPLS to analyze data collected from 238 respondents who use Trans Jatim bus services. This study was conducted in two stages: first exploring primary variables, followed by an in-depth analysis of digital payment technology using the UTAUT2 method. Findings – The results show that digital payment and accessibility have a positive effect on passenger satisfaction and service quality. Digital payment methods improve service quality and passenger satisfaction, while accessibility directly increases passenger satisfaction. In addition, service quality acts as an intervening variable between digital payment or accessibility and passenger satisfaction. While social influence does not have a significant impact on the use of digital payments. Originality – Unlike previous studies that examined these factors in isolation, this research integrates them using the UTAUT2 model. Furthermore, this study offers practical insights for policymakers in improving urban mobility and transportation services by leveraging digital payment systems and enhancing accessibility. This dual focus on technological and service quality improvements provides a comprehensive framework for sustainable public transportation systems in emerging economies.